Linking tree-ring growth and satellite-derived gross primary growth in multiple forest biomes. Temporal-scale matters. (January 2020) - Vicente-Serrano, Sergio M.; Martín-Hernández, Natalia; Camarero, J. Julio; Gazol, Antonio; Sánchez-Salguero, Raúl; Peña-Gallardo, Marina; El Kenawy, Ahmed; Domínguez-Castro, Fernando; Tomas-Burguera, Miquel; Gutiérrez, Emilia; de Luis, Martin; Sangüesa-Barreda, Gabriel; et al.
Highlights: Positive and significant relationship between the interannual variability and the secondary growth. Similar average correlations among all different forest types. Maximum correlations found between NDVI and tree-ring growth are recorded considering cumulative NDVI values. Temporal lags may be expected due to particular physiological processes. Abstract: This study links tree-ring growth and gross primary production for a variety of forest types under different environmental conditions across Spain. NOAA-AVHRR satellite imagery data were combined with dendrochronological records and climate data at a fine spatial resolution (1.21 km 2 ) to analyze the interannual variability of tree-ring growth and vegetation activity for different forest biomes from 1981 to 2015. Specifically, we assessed the links between tree-ring width indices (TRWi), the Normalized Difference Vegetation Index (NDVI) and a variety of environmental conditions, represented by climatic variables (air temperature, precipitation, evapotranspiration and water balance) and elevation. The impact of these variables on tree growth was assessed by means of the Predictive Discriminant Analysis (PDA). Results reveal a general positive and significant relationship between inter-annual variability of the NDVI at a high spatial resolution (1.21 km 2 ) and tree-ring growth. Maximum correlations between NDVI and tree-ring growth were recorded when cumulative NDVI values were considered, in some cases covering long time periods (6–10 months), suggesting that tree growth is mainly related to Gross Primary Production (GPP) at annual scale. The relationship between tree-ring growth and inter-annual variability of the NDVI, however, strongly varies between forest types and environmental conditions.